Literacy in Primary School and its Transformations under ICT Incorporation (Papeles, 2014)
This article is the result of a theoretical review related to the conceptualization and practices of literacy from the XIX century, until today. It aims to encourage reflection and provide some strategies for teaching, taking into account the changes caused by the incorporation of ICT in school and society in general. It argues that the literacy process developed at school must lead the student to uncover the meaning of text that he/she reads and develop certain semantic and morpho-syntactic structures to facilitate and promote the textual production. Linking ICT in this process fosters student interest and promotes contact with the world. However, this link must be into a planning and ongoing teacher guidance aimed towards achieving progress and development of thinking skills.
Keywords: reading; writing; grammar; text linguistics; text production; teacher; ICT